How Asian countries understand policy experiment as policy pilots?. Issue 3 (2nd September 2017) - Ko, Kilkon; Shin, Kayoung
ABSTRACT: Policymaking based on the classical experimental design is regarded as a golden rule in the field of public policy. Despite the methodological superiority of randomized control experiment, the practices of policy experiment differ across countries, reflecting the different intentions of policymakers. This paper reviews how policy experiments are practised in Asian countries, especially Korea, China, and Singapore. As our review suggests, the term 'policy pilot' is preferred to 'experiment' as the former is considered as an exemplar proposed by the central government. At the same time, the selection of pilot sites depends on central government's political and practical (rather than methodological) consideration. Moreover, the utilization of policy pilots does not solely depend on the success of the pilot programme or the effect size per se. As the policymaking process is a complex endeavour involving multiple streams of actors, resources, and solutions, Asian countries use policy pilot results to get ideas on how different actors respond to policy, instead of a determinant of policy decision. Therefore, we conclude that Asian countries emphasize less the rigorousness of experimental design than the possibility of pragmatic utilization of policy pilots.